Pengembangan Usaha Petani Sayur untuk Meningkatkan Perekonomian Masyarakat Desa Bulotalangi Timur” - Erni Mohamad; Perry Zakaria; Fauziah N Kasim; Widya A Habi; Rahmat S Napu; Lilis Anggraini; Priska Paramata (Universitas Negeri Gorontalo, 2022)
This service activity aims to provide education to farmers and housewives in an effort to develop vegetable farming businesses. So far, vegetables that have only been consumed or marketed to the general public can be converted into other ingredients. The people of this village do not yet understand that these vegetables, especially the produce of kale and spinach vegetable farmers, can be used as other ingredients in the form of snacks, namely as sticks and noodles. The processing process does not require a lot of money, but when it is marketed it will be able to increase the economic value of the community. The method used is direct training to groups of housewives and vegetable farmers with innovative technology. From the results of the implementation of this activity, the community was very enthusiastic about participating in the activity and was interested in making/producing kangkong chips and spinach noodles themselves. The community also suggested that they would make a business in the form of snacks as well, apart from those made from kale and spinach, according to their statements after participating in the training activities